Impact, feasibility, and acceptability of CREATORS: An arts-based pilot intervention to reduce mental-health-related stigma among youth in Hyderabad, India - Shivani Mathur Gaiha; Antonio Gasparrini; Mirja Koschorke; Usha Raman; Mark Petticrew; Tatiana Taylor Salisbury (Elsevier, 2024)
Background: Mental-health-related stigma prevents youth from seeking help for mental health problems. Limited studies in low- and middle-income countries assess the effect of arts-based education in reducing such stigma among youth, thereby leaving a gap in evidence-based, age- and culturally-appropriate interventions. Objective: To evaluate the impact, feasibility, and acceptability of CREATORS, an arts-based educational program on reducing mental-health-related stigma among youth in India. Methods: We conducted a mixed-methods, pre-post control group study among college-going adolescents in Hyderabad, India. At baseline and post-intervention (after six weeks), we examined differences in intended behavior towards people with mental health problems. Results: Our study involved 432 participants across three study groups: participants creating art on the theme of mental-health-related stigma over six weeks (n = 123), a student audience viewing 2-h arts show by participants (n = 244), and a control group (n = 65). Between baseline and post-test, participants creating art showed significantly lower stigma towards people with mental health problems compared to members of the control group (coefficient = 1.55, 95%CI 0.06-3.04, p = 0.041). Participants found the intervention useful and enjoyable (>95%; n = 773 across six weeks). Participants identified that collaborative creation of art made the subject of mental health interesting and relatable. Conclusions: Participating in an arts-based educational program was associated with significantly lower mental-health-related stigma among youth compared to a control group in the short term. High acceptability of the program demonstrates the utility of arts-based education to address mental-health-related stigma. With community partners and artists as facilitators, our program may support mental health specialists in mental health promotion.